FORMULATION DESIGN AND CHARACTERIZATION OF ROPINIROLE HYDROCHORIDE MICROSPHERE FOR INTRANASAL DELIVERY - Mantry, Shubhrajit; Balaji, Anna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this research work to design nasal microspheres of ropinirole hydrochloride (HCL) using different mucoadhesive polymers by adopting the suitable technique. To study the influence of formulation and process variables on microsphere formation and release characteristics. To perform the physicochemical characterization of the prepared microspheres. To carry out in vitro drug release studies and to explore the release behavior using various kinetic models. Methods: Experiments were performed with ropinirole HCL as a drug, chitosan, guar gum, carbopol 974P as a polymer. Span 80 and Tween 80 used light liquid paraffin, concentrated hydrochloric acid as solvent. Result: The in vitro drug release studies were conducted for all the formulations, that is, F1-F21 in 250 ml phosphate buffer pH 6.6 for 12 hrs. Among them, F15 showed 82.7Â±0.23% drug release and F21 showed 81.2% in 12 hrs in a sustained manner. Conclusion: Microspheres were formulated by emulsion solvent evaporation technique using different polymers. Apart from preventing nasal irritation, the microsphere possesses two major advantages over plain solutions, one is a high solubilization capacity for ropinirole HCL that exceeds their aqueous solubility and thus allows a reduction in the application volume. The results of this work indicate that intranasal microsphere of ropinirole may be beneficial for the treatment of Parkinson's disease.